Overexpression of the carbohydrate binding module from Solanum lycopersicum expansin 1 (Sl-EXP1) modifies tomato fruit firmness and Botrytis cinerea susceptibility - Perini, Mauro Alejandro (2017)
Firmness, one of the major determinants of postharvest quality and shelf life of fruits is determined by the mechanical resistance imposed by the plant cell wall. Expansins (EXP) are involved in the nonhydrolytic metabolic disassembly of plant cell walls, particularly in processes where relaxation of the wall is necessary, such as fruit development and ripening. As many carbohydrate-associated proteins, expansins have a putative catalytic domain and a carbohydrate-binding module (CBM). Several strategies have been pursued to control the loss of fruit firmness during storage. Most of the approaches have been to suppress the expression of key enzymes involved in the cell wall metabolism, but this is the first time that a CBM was overexpressed in a fruit aimed to control cell wall degradation and fruit softening. We report the constitutive overexpression of the CBM of Solanum lycopersicum expansin 1 (CBMSlExp1) in the cell wall of tomato plants, and its effects on plant and fruit phenotype. Overexpression of CBM-SlExp1 increased the mechanical resistance of leaves, whereas it did not modify plant growth and general phenotype. However, transgenic plants showed delayed softening and firmer fruits. In addition, fruits were less susceptible to Botrytis cinerea infection, and the “in vitro” growth of the fungus on media containing AIR from the pericarp of transgenic fruits was lower than controls. The possibility of overexpressing a CBM of a fruit-specific expansin to control cell wall degradation and fruit softening is discussed.